2018
DOI: 10.1177/1753425918801496
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal dysbacteriosis activates tumor-associated macrophages to promote epithelial-mesenchymal transition of colorectal cancer

Abstract: In this study we investigated the association between intestinal dysbacteriosis with colorectal cancer progress and the underlying molecular mechanisms. Tumor progression was evaluated using xenograft mice model. The epithelial-mesenchymal transition (EMT) markers were quantified by both real-time PCR and immunoblotting. The serum content of IL-6 and TNF-α were measured with ELISA kits. Cell proliferation was determined by the Cell Counting Kit-8. Intestinal dysbacteriosis was successfully simulated by the adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…On the other hand, the antibiotics used did not influence the serum TNF-α levels of the mice. These results agree with those of previous studies in which antibiotic use also increased serum IL-6 in mice suffering from microbiota dysbiosis induced by antibiotics [ 38 ]. Heat-inactivated Lactobacillus rhamnosus GG and Lactobacillus delbrueckii subsp.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the antibiotics used did not influence the serum TNF-α levels of the mice. These results agree with those of previous studies in which antibiotic use also increased serum IL-6 in mice suffering from microbiota dysbiosis induced by antibiotics [ 38 ]. Heat-inactivated Lactobacillus rhamnosus GG and Lactobacillus delbrueckii subsp.…”
Section: Discussionsupporting
confidence: 93%
“…Dual [28][29,30] ↓ in tumor under immunotherapy [33] ↑ in serum [74] ↓ by FMT under DSS [27] NF-κB Promote [ ↑ [134] ↓ in colon [94] ↑ by FMT [27,94,95] IL-17 Promote [106,135][114,135] ↓ in CD4 + T cell [113] ↓ in colon [94] ↓ by FMT under DSS [75] IFNs Suppress (α, β) [122] Controversial (γ) [124,129,130] ↓ IFNAR1 [122] ↓ α, β in ileum under viral infection [131] ↓ γ in T cells under viral infection [132] ↓ β, γ in SI under T. gondii infection [60] ↑ γ by L. delbrueckii, S. thermophilus under DMH-induced CRC [133] ↓ γ by FMT under DSS [75] ↑, up-regulated; ↓, down-regulated; CRC, colorectal cancer; GF, germ-free; ABX, antibiotics cocktail; TNF, tumor-necrosis factor; FMT, fecal microbiota transplantation; DSS, dextran sulfate sodium; NF-κB, nuclear factor kappa B; P. anaerobius, Peptostreptococcus anaerobius; IL-1, interleukin-1; LP, lamina propria; SI, small intestine; T. gondii, Toxoplasma gondii; VSL#3, probiotic mixture; CD, Crohn's disease; IL-6, interleukin-6; UC, ulcerative colitis; LPS, lipopolysaccharide; IL-10, interleukin-10; IL-17, interleukin-17; IFNs, interferons; IFNAR, interferon-α/β receptor; L. delbrueckii, Lactobacillus delbrueckii; S. thermophilus, Streptococcus thermophilus; DMH, 1,2-dimethylhydrazine.…”
Section: Tnfmentioning
confidence: 99%
“…It was found that LPS-induced IL-6 secretion was inhibited in the group treated with the bacterial mixture compared to that in the control [ 73 ]. ABX treatment upregulated the serum concentration and macrophage expression of IL-6 compared to the values in control mice with HT29 CRC xenografts [ 74 ]. Burrello et al evaluated the effects of FMT in chronic intestinal colitis induced via three cycles of 7-day DSS treatment.…”
Section: Microbiota Inflammatory Mediators and Crcmentioning
confidence: 99%
“…Multiple lines of evidence indicate the existence of a tight relationship between enteric bacteriome, macrophages, and tumor promotion [ 96 ]. Macrophages of mice with intestinal dysbacteriosis release pro-tumorigenic cytokines (e.g., IL-6 and TNF) and stimulate in vivo the growth of tumor xenografts, while promoting colon cancer cell proliferation and EMT in vitro [ 101 ]. Notably, depletion of macrophages totally abrogates the pro-tumor effect of intestinal dysbacteriosis, indicating that bacteria require macrophages to exert pro-tumor activities [ 101 , 102 ].…”
Section: Cross-talk Between Gut Microbiota and Macrophages In Crc mentioning
confidence: 99%
“…Macrophages of mice with intestinal dysbacteriosis release pro-tumorigenic cytokines (e.g., IL-6 and TNF) and stimulate in vivo the growth of tumor xenografts, while promoting colon cancer cell proliferation and EMT in vitro [ 101 ]. Notably, depletion of macrophages totally abrogates the pro-tumor effect of intestinal dysbacteriosis, indicating that bacteria require macrophages to exert pro-tumor activities [ 101 , 102 ]. Moreover, macrophages can drive alterations of the microbial profile associated with CRC promotion.…”
Section: Cross-talk Between Gut Microbiota and Macrophages In Crc mentioning
confidence: 99%